T cell receptor and coreceptor CD8 alphaalpha bind peptide-MHC independently and with distinct kinetics. - Wyer, JR; Willcox, B; Gao, G; Gerth, U; Davis, S; Bell, J; Van Der Merwe, P; Jakobsen, B (1999)
The T cell surface glycoprotein CD8 enhances T cell antigen recognition by binding to MHC class I molecules. We show that human CD8 alphaalpha binds to the MHC class I molecule HLA-A2 with an extremely low affinity (Kd approximately 0.2 mM at 37 degrees C) and with kinetics that are between 2 and 3 orders of magnitude faster than reported for T cell receptor/peptide-MHC interactions. Furthermore, CD8 alphaalpha had no detectable effect on a T cell receptor (TCR) binding to the same peptide-MHC class I complex. These binding properties provide an explanation as to why the CD8/MHC class I interaction is unable to initiate cell-cell adhesion and how it can enhance TCR recognition without interfering with its specificity.